40Ar/39Ar hornblende and biotite geochronology of the Bulfat Igneous Complex, Zagros Suture Zone, NE Iraq: New insights on complexities of Paleogene arc magmatism during closure of the Neotethys Ocean - Aswad, K.; Ali, S.; Al.Sheraefy, R.; Nutman, A.; Buckman, S.; Jones, B.; Jourdan, Fred (Elsevier BV, 2016)
In NE Iraq, the eastern edge of the Arabian plate is overlain by arc rock allochthons whose genesis and tectonic emplacement were related to the consumption and closure of the Neotethys Ocean. This paper demonstrates the occurrence of unrelated Paleogene arc rocks in two adjacent allochthons. The Bulfat Igneous Complex at Wadi Rashid (NE Iraq) is an intrusion within the Upper Allochthon Albian–Cenomanian Gimo–Qandil sequence suprasubduction zone assemblage. A thrust separates this allochthon from the underlying Lower Allochthon of the Eocene-Oligocene Walash–Naopurdan volcanic-sedimentary arc rocks. The Bulfat Igneous Complex at Wadi Rashid consists of gabbro and granitic composite intrusions in which components mingle down to a small scale. Textural relationships in the Bulfat Igneous Complex rocks indicate emplacement at high crustal levels with rapid cooling, which is consistent with amphibole geobarometry indicating crystallisation pressures between ~ 250 and 300 Mpa. Ti-rich igneous pargasite and Ti-rich igneous Fe-biotite from gabbroic and granitic components yielded 40Ar/39Ar ages of 39.23 ± 0.21 and 38.87 ± 0.24 Ma respectively. These ages agree within analytical error and suggest coeval emplacement and rapid cooling of mafic and felsic magmas in the Eocene, in an event that was distinct and much younger than the host Albian–Cenomanian rocks. This igneous event was unrelated to formation of Cenozoic rocks in the underlying, tectonically separate, lower allochthon. The trace element signatures of the Wadi Rashi volcanic rocks show volcanic-arc characteristics for the granites and the gabbroic rocks resemble E type MORB. The presence of Eocene arc-related rocks in two allochthons suggests complexity in Paleogene subduction systems, with possibly two subduction zones operating at that time.